Reconstructie van het ontstaan van de verzameling hoogleraarsportretten van de Vrije Universiteit Amsterdam - Harinck, George (Studium, 2018)
this article offers a reconstruction of the beginning of the professor’s portraits gallery of the Vrije Universiteit Amsterdam, founded in 1880. With this collection, the university joined a long academic tradition. the beginning of the collection was the gift of the family of the main founder of the university, Abraham kuyper. After he died in 1920, his heirs donated two painted portraits from his legacy to the Vrije Universiteit, one of their father, and the other of his collega proximus F.L. rutgers. the latter was not painted by Jozef Israëls, as has been suggested sometimes, but was a copy of the reputed original by another painter. After this gift, the university decided that portraits of the other profes- sors of the first generation should also be collected. In the 1930s, the university had obtained six portraits, all of them offered to them by pupils of one of the first professors or by their sympathizers.